Are Laurence Sterne's Sermons Funny? - Stark, Ryan J. (2016)
Laurence Sterne's sermons are earnest in the way we expect eighteenth-century Anglican sermons to be earnest, and the humour is relatively scarce and appropriate, or appropriately inappropriate, as the case might be. Regardless, I show that the humour is there, contrary to the widely held view that Sterne's sermons do not amuse. Moreover, some of the comic passages point to a neglected but crucial source of inspiration for Sterne's comic genius: the Bible, especially the Old Testament-that ancient repository of wisdom and proto-Shandean intrigue.